2020
DOI: 10.5603/fhc.a2019.0019
|View full text |Cite
|
Sign up to set email alerts
|

MiR-539-5p alleviates sepsis-induced acute lung injury by targeting ROCK1

Abstract: Introduction. Sepsis-induced acute lung injury (ALI) is an inflammatory process involved with simultaneous production of inflammatory cytokines and chemokines. In this study, we investigated the regulatory role of miR-539-5p in sepsis-induced ALI using a mouse model of cecal ligation puncture (CLP) and an in vitro model of primary murine pulmonary microvascular endothelial cells (MPVECs). Material and methods. Adult male C57BL/6 mice were intravenously injected with or without miR-539-5p agomir or scrambled co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…A recent study has indicated that miR-802 was expressed at a low level in LPS-induced ALI and alleviated LPS-induced ALI by targeting Peli2 (20). Another recent study has revealed that miR-539-5p was underexpressed in sepsis-induced ALI and could protect mice from ALI (21). In the present study, the expression of miR-26a-5p was downregulated in LPS-induced ALI models in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A recent study has indicated that miR-802 was expressed at a low level in LPS-induced ALI and alleviated LPS-induced ALI by targeting Peli2 (20). Another recent study has revealed that miR-539-5p was underexpressed in sepsis-induced ALI and could protect mice from ALI (21). In the present study, the expression of miR-26a-5p was downregulated in LPS-induced ALI models in vivo and in vitro.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have indicated that ALI is featured with the production of inflammatory factors, inflammatory cell infiltration and pulmonary epithelial cell apoptosis (24,25). Evidence from several clinical studies has indicated that TNF-α, IL-1β and IL-6 are the main inflammatory cytokines actively secreted in response to the inflammatory cascade in ALI (21,26). Previous studies have indicated that the excess inflammatory cytokines, such as TNF-α, IL-6 and IL-1β, ultimately cause cell death via apoptosis and pyroptosis (27).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins extracted from MPVEC lysates were analysed by 8% SDS‐PAGE gel and transferred to PVDF membranes as previously described 22 . Then, membranes were incubated with primary antibodies (1:1000, Abcam) for 6 hours at 4°C, including p‐AKT, AKT and β‐actin.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, multiple miRNAs have been revealed to regulate inflammation in ALI. Meng et al (29) revealed that miR-539-5p relieved sepsis-induced ALI by targeting the protein Rho associated coiled-coil containing protein kinase 1. Yang et al (30) revealed that miR-142a-3p alleviated ALI induced by E. coli lipopolysaccharides by acting on TGF-β-activated kinase 1 and MAP3K7-binding protein 2.…”
Section: Discussionmentioning
confidence: 99%